PREPARATION AND FIBER FRACTURE OF METAL MATRIX COMPOSITE FEED-STOCK FOR POWDER INJECTION MOLDING. - ., Faiz Ahmad, Muhammad Rafi Raza, Ali Samer Muhsan, Mohd Afian Ome (2013)
n this study, the preparation of a range of metal matrix composite feedstocks and their characterization are presented. In order to achieve a uniform dispersion of metal powder and fibers in the binder, a co-rotating twin-screw extruder was used for feedstock preparation. Three formulations consisting of aluminum powder and fiberglass were developed and another three were prepared using aluminum powder and silicon carbide fibers mixed with binder. A capillary rheometer was used to measure melt shear stress and the corresponding fiber fractures were analyzed. Scanning electron microscopy (SEM) was used to determine the dispersion of powder and fibers in the mixes. Optical imaging was utilized to measure fiber fracture in the composite mixes. The viscosity of the mixes, fiber content, and shear rate are contributing factors in fiber fracture during compounding. Melt shear stress was calculated for various aspect ratios of the fibers and it was found to increase with the aspect ratio of the fibers.